Estudio morfológico del páncreas en alpacas (Vicugna pacos) jóvenes y adultas - Panesi A., Gianmarco (2018)
The aim of this study was to morphologically characterize the pancreas of young (n=9) and adult (n=5) alpacas. In the macroscopic study, the pancreas was observed in situ to determine the shape and its relationship with other organs. In the microscopic study, routine histologic procedures were applied and histological sections of 5 µm thick were stained with Mayer-Eosin hematoxylin and Masson trichrome. The pancreas is divided in three sections: body, right lobe and left lobe which extend to the left plane, bordering the spleen and in greater proportion to the descendant colon. The hepatopancreatic duct presented two origins; one where the hepatic duct enters the pancreatic parenchyma and it leaves by the right lobe as the hepatopancreatic duct and another where the pancreatic duct joins with the hepatic duct as it emerges from the right lobe to form the hepatopancreatic duct. In the microscopic evaluation was observed that the pancreatic parenchyma is surrounded by a thin layer of connective tissue formed mostly by collagen fibers, which invaginate within the parenchyma forming lobes and pseudolobules, as well as cells with pyramidal shape accommodated in the form of acini. In the parenchyma was observed the islets of Langerhans randomly distributed. The intralobular and interlobular ducts were formed by simple cubic epithelium, and the hepatopancreatic duct was formed by an extensive irregular mucosa covered with columnar epithelium with microvilli. It is concluded that the alpaca pancreas shows morphological differences with other species such as ruminants, herbivores and domestic carnivores.